Strategi Komunikasi antara Suplier dengan Retail dalam Membangun Hubungan yang Baik - Bryan, Bryan; Setyanto, Yugih (Kiwari, 2025)
Suppliers are responsible for providing products that meet consumer needs through retail networks, while retailers act as intermediaries between suppliers and end consumers. This relationship can be mutually beneficial if managed effectively through proper communication. Suppliers can enhance their product distribution, while retailers can gain profits by ensuring timely product availability. This study employs a qualitative approach using descriptive methods, enabling researchers to understand the meaning behind the dynamics of the supplierretailer relationship. Data was collected through triangulation techniques, and the analysis was conducted inductively, emphasizing meaning over generalization. The findings highlight the importance of maintaining good and sustainable collaboration through both professional and personal approaches. Professional relationships involve consistent responses to inquiries, prompt problem resolution, and high-quality service delivery. Additionally, programs such as promotions and incentives can enhance retailer satisfaction. Transparency in addressing technical and administrative challenges is also essential to building trust. This trust serves as the foundation for progressing to the next stage, which involves establishing deeper personal relationships to strengthen long-term cooperation between suppliers and retailers. Suplier bertanggung jawab menyediakan produk yang memenuhi kebutuhan konsumen melalui jaringan retail, sedangkan retail berperan sebagai penghubung antara suplier dan konsumen akhir. Hubungan ini dapat saling menguntungkan, jika dikelola dengan komunikasi yang efektif. Suplier dapat meningkatkan distribusi produknya, sementara retail dapat memperoleh keuntungan dengan menyediakan produk yang tepat waktu. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif, yang memungkinkan peneliti memahami makna di balik dinamika hubungan antara suplier dan retail. Data dikumpulkan melalui teknik triangulasi, dan analisis dilakukan secara induktif dengan penekanan pada makna daripada generalisasi. Hasil penelitian menunjukkan pentingnya memelihara hubungan kerja sama yang baik dan berkelanjutan melalui pendekatan profesional dan personal. Hubungan profesional melibatkan respons konsisten terhadap pertanyaan, penanganan cepat terhadap masalah, dan pemberi layanan yang berkualitas. Kegiatan promosi dan insentif dapat meningkatkan kepuasan retail. Keterbukaan dalam menyampaikan kendala teknis dan administratif juga penting untuk membangun kepercayaan. Kepercayaan ini menjadi dasar untuk melangkah ke tahap berikutnya, yaitu membangun hubungan personal yang mendalam untuk memperkuat kerja sama jangka panjang antara suplier dan retail.